Trajectories of pain and function in the first five years after total hip and knee arthroplasty: an analysis of patient reported outcome data from the National Joint Registry - Dainty, JR; Smith, TO; Clark, EM; Whitehouse, MR; Price, AJ; MacGregor, AJ (British Editorial Society of Bone and Joint Surgery, 2021)
Aims To determine the trajectories of patient reported pain and functional disability over five years following total hip arthroplasty (THA) or total knee arthroplasty (TKA).